The Implementation of a Local Wisdom-Based English Learning Model to Improve Students’ English Proficiency at SDN 11 Mengkendek Tana Toraja - Viktor Siumarlata; Rachel Rachel; Matius Tandikombong; Selviana Songgo (Universitas Cokroaminoto Palopo, 2026)
This study investigated the effectiveness of a local wisdom-based English learning model in enhancing the English proficiency of fifth-grade students at SDN 11 Mengkendek, Tana Toraja, Indonesia. The model integrates Torajan cultural values into English instruction to provide students with meaningful and contextually relevant learning experiences. Employing a quantitative experimental design with a one-group pretest–posttest approach, the study involved 23 participants selected through cluster sampling. Data were collected using an English proficiency test measuring vocabulary and sentence structure, while data analysis was conducted using PSPP software. Statistical analyses included descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon Signed-Rank Test, and the calculation of effect size (r). Results revealed a significant improvement in students’ posttest scores (Z = −4.02, p = 0.000), with a very large effect size (r = 0.84), indicating that the model had a substantial pedagogical impact. The findings affirm that embedding local culture such as the Torajan values of kasianggaran, kasiuluran, and kasialamasean into English learning fosters stronger engagement, comprehension, and cultural identity. This study supports the principles of Contextual Teaching and Learning (CTL) and highlights the importance of culturally responsive pedagogy in improving English education within Indonesia’s multicultural settings.